2018
DOI: 10.1097/01.nep.0000000000000385
|View full text |Cite
|
Sign up to set email alerts
|

Constructive Feedback Teaching Strategy

Abstract: Viewing this teaching strategy enabled nursing students to develop an awareness of the opportunity that constructive feedback presents for professional development, self-improvement, teamwork and collaboration, and patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…These findings are consistent with past studies, suggesting that training students in peer feedback skills supports production of high-quality peer feedback. 21,22 In addition, this study extends previous research by providing objective data related to learning outcomes in terms of knowledge and quality of feedback. Moreover, it contributes evidence to support the essential role of value in increasing the likelihood students will provide high-quality feedback in authentic peer-review contexts.…”
Section: Discussionmentioning
confidence: 57%
“…These findings are consistent with past studies, suggesting that training students in peer feedback skills supports production of high-quality peer feedback. 21,22 In addition, this study extends previous research by providing objective data related to learning outcomes in terms of knowledge and quality of feedback. Moreover, it contributes evidence to support the essential role of value in increasing the likelihood students will provide high-quality feedback in authentic peer-review contexts.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, engaging students in discussions around their self-recorded videos allowed students to compare their own performances against their peers, as well as reflect on improving their own skills. Students were also able to practice providing and receiving constructive feedback, which is an important quality that is necessary for ongoing development [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is aligned with another study in which nursing students identified receipt of constructive feedback as an opportunity for improvement in professional performance and patient safety. 8 Students also expressed a desire to engage in a fair exchange of high-quality peer feedback. Students who had a higher sense of value for providing peer feedback tended to cite a goal to help their peers in advance of confirmation of a fair exchange of high-quality feedback (sometimes referred to as "paying it forward"), whereas students with a lower sense of value for providing peer feedback were less optimistic about receiving a fair exchange of effort and quality in peer review and feedback.…”
Section: Discussionmentioning
confidence: 99%
“…7 Students who value the peer feedback process are more likely to invest time and effort in transferring peer review knowledge and skills to real-world contexts. 8 Therefore, a deeper understanding of the motivating forces for students who transfer knowledge about peer feedback and apply peer-review skills in authentic contexts will help faculty plan educational opportunities that promote a strong sense of value for providing supportive peer feedback among all students. Ultimately, exchange of high-quality peer feedback in well-designed peer review activities will support development of self-regulation in learning, deeper student engagement with performance standards, and effective collaboration in high-functioning teams.…”
Section: Nurse Educatormentioning
confidence: 99%